2015
DOI: 10.1051/0004-6361/201526797
|View full text |Cite
|
Sign up to set email alerts
|

Planckrevealed bulk motion of Centaurus A lobes

Abstract: Planck data towards the active galaxy Centaurus A are analyzed in the 70, 100 and 143 GHz bands. We find a temperature asymmetry of the northern radio lobe with respect to the southern one that clearly extends at least up to 5• from the Cen A center and diminishes towards the outer regions of the lobes. That transparent parameter -the temperature asymmetry -thus has to carry a principal information, i.e. indication on the line-of-sight bulk motion of the lobes, while the increase of that asymmetry at smaller r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Planck data confirmed the effect for the M31 halo, and helped to study its rotational dynamics [10]. After that, Planck data allowed studying the dynamics of various other galaxies and their halos [11,12,16,17]. The composition, constituents and dynamics of the halo are obviously very difficult to determine.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Planck data confirmed the effect for the M31 halo, and helped to study its rotational dynamics [10]. After that, Planck data allowed studying the dynamics of various other galaxies and their halos [11,12,16,17]. The composition, constituents and dynamics of the halo are obviously very difficult to determine.…”
Section: Introductionmentioning
confidence: 93%
“…We have used the data published in the literature for the various galaxies[11,12,16,17] in the 70 GHz, 100 GHz, and 143 GHz bands at resolution corresponding to N side = 2048 in HEALPix scheme[15]. The temperature excesses are shown inTable 2(column 4).…”
mentioning
confidence: 99%
“…The study of the Planck data 1 in several microwave bands had revealed temperature asymmetry for several nearby edge-on spiral galaxies extending to their halos. [2][3][4][5][6] That asymmetry is frequency independent, thus indicating its Doppler nature. Previously we have studied 7 that effect based on the microwave data for the galaxy M31, namely, regarding the possible contribution of the thermal dust in the rotation of the halo.…”
Section: Introductionmentioning
confidence: 96%
“…We have calculated the temperature asymmetry values using the methods of. [2][3][4][5][6] The paper is organized as follows: Sections 2 and 3 describe dust emission properties and velocities for M82, M81 galaxies, respectively. In Section 4 we briefly discuss certain modified gravity models proposed to explain the dark matter paradigm including the model in.…”
Section: Introductionmentioning
confidence: 99%
“…3 Among the recent studies addressing the structure of galactic halos are those based on the analysis of the microwave temperature asymmetry of nearby galaxies using several frequency bands of the Planck data. [4][5][6][7][8] Namely, first for M31, then for several other Local Supercluster spiral edge-on galaxies it was shown that, the temperature asymmetry both in the disk and halo extends up to 130kpc. While the essentially frequency independent temperature asymmetry is indicating the Doppler nature of the effect, the Doppler induced anomaly itself can be due to different emission mechanisms of interstellar medium (ISM).…”
Section: Introductionmentioning
confidence: 99%